Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Werabe University - International Livestock Research Institute; Werabe University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Werabe University. On March 30, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Towfik Jemal, President of Debark University.